Recoil-ion momentum spectroscopy for cold rubidium in a strong femtosecond laser field - Li, Renyuan; Weidemüller, Matthias (Journal of Instrumentation, 2019)
In this study, a new magneto-optical trap (MOT) recoil ion momentum spectrometer is built for investigating the interactions between cold rubidium (Rb) atoms and strong laser fields. This compact device can provide cold Rb in three different modes: 2D MOT mode, in which the beam generated by a two-dimensional MOT is pushed directly to the interaction regime; molasses mode, in which cooling lasers are applied at the interaction regime; and 3D MOT mode, in which a quadrupole magnetic field is applied to form a three-dimensional MOT. The typical densities of the three target modes are estimated to be 107, 108, and 109 atoms/cm3, respectively. Switching between the target modes is expected to provide a broad range of laser intensities with reasonable count rates while avoiding space charge effects. A single photoionization experiment serves as a benchmark test of the recoil ion momentum resolution. The best resolution is estimated as an unprecedented 0.12 a.u. in the time-of-flight direction, demonstrating significant potential for strong field ionization dynamics using this technique.
Gesehen am 16.05.2019